Wages in the Theoretical Perspectives and Islam - Muslimin, JM; Etika, Nurul (Universitas Islam Negeri Raden Intan Lampung, 2020)
Wages are a very basic value in business transactions. In wage agreements, the pattern and nature of the relationship between employers and workers can easily be identified. Unfair and exploitative wages occur because contracts are not open, lack transparency, and are not based on equality, understanding, and willingness. In the Marxist perspective, wages are always placed on suspicion of containing elements and relations of exploitation by the strong against the weak. In this context, transactions and wages are colored by capitalist elements and motives. Islam views wages as a gift from the Almighty which must be implemented in an affective-humanist manner. Although there are differences in roles between workers and employers, the answers to the material agreement are that of equality, openness, and willingness. On the other hand, at the same time, this principle is expected to make the character of work interconnected to make work relationships more conducive.